Implications of ACMG guidelines to identify high-risk acute lymphoblastic leukemia patients with hereditary cancer susceptibility syndromes (HCSS) in a highly consanguineous population - Sara Aslam; Shabana; Mehboob Ahmed (BMC, 2021)
Abstract Background Hereditary cancer susceptibility syndrome (HCSS) contributes to the cancer predisposition at an early age, therefore, identification of HCSS has found to be crucial for surveillance, managing therapeutic interventions and refer the patients and their families for genetic counselling. The study aimed to identify ALL patients who meet the American College of Medical Genetics (ACMG) criteria and refer them for the genetic testing for HCSS as hereditary leukemia and hematologic malignancy syndrome, and to elucidate the significance of high consanguinity with the prevalence of inherited leukemia in Pakistani population. Methods A total of 300 acute lymphoblastic leukemia patients were recruited from the Children's Hospital, Lahore, Pakistan from December 2018 to September 2019. A structured self-reporting questionnaire based on family and medical history of the disease was utilized for the data collection. Results In our cohort, 60.40% of ALL patients were identified to meet ACMG criteria. Among them, a large number of patients (40.65%) solely fulfil the criteria due to the presence of parental consanguinity. However, parental consanguinity showed protective impact on the onset at early age of disease [OD = 0.44 (0.25-0.77), p-value = 0.00] while, a family history of cancer increased the risk of cardiotoxicity [OD = 2.46 (1.15-5.24), p-value = 0.02]. Parental consanguinity shows no significant impact on the family history of cancer and the number of relatives with cancer. Conclusions More than 50% of the ALL patients were considered the strong candidates' for genetic testing of HCSS in the Pakistani population, and parental consanguinity was the leading criteria fulfilled by the individuals when assessed through ACMG guidelines. Our study suggests revisiting ACMG guidelines, especially for the criterion of parental consanguinity, and formulating the score based criteria based on; genetic research, the toxicology profile, physical features, personal and family history of cancer for the identification of patients for the genetic testing.